2018
DOI: 10.5664/jcsm.6942
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating DSM-5 Insomnia Disorder and the Treatment of Sleep Problems in a Psychiatric Population

Abstract: With the new calling from DSM-5, clinicians treating psychiatric patients should view insomnia less as a symptom of their mental illnesses and treat clinical insomnia as a primary disorder. Patients should also be educated on the importance of reporting and treating their sleep complaints. Nonmedical (cognitive and behavioral) interventions for insomnia need to be further explored given their proven clinical effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 47 publications
1
47
0
1
Order By: Relevance
“…There is a gender imbalance in our insomniacs and non-insomniacs group with the significantly prevalent female population among those reporting insomnia symptoms. However, it corresponds to other studies data which showed that women are more likely to have lower sleep quality and shorter sleep [7,23].…”
Section: Study Limitationssupporting
confidence: 90%
See 1 more Smart Citation
“…There is a gender imbalance in our insomniacs and non-insomniacs group with the significantly prevalent female population among those reporting insomnia symptoms. However, it corresponds to other studies data which showed that women are more likely to have lower sleep quality and shorter sleep [7,23].…”
Section: Study Limitationssupporting
confidence: 90%
“…However, there is lack of evidence of the relation between insomnia and vascular atherosclerotic involvement. There are only few studies assessing the presence of subclinical atherosclerosis in insomniacs, and their data are highly controversial [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…International studies on insomnia among the population with severe mental disorders, and specifically among people with schizophrenic disorder who undergo follow-up and monitoring at outpatient centers, report varying results depending on the diagnostic criteria applied and the diagnostic tool used, either the most frequently used manuals, such as the ICD-10, DSM-IV or ICSD-2, or the most current, like the DSM-V or ICSD-3 [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Det er vist at forekomsten av klinisk signifikant angst og depresjon er 10-17 ganger høyere blant personer med insomni sammenliknet med personer uten insomni (4). Samtidig er det vist at forekomsten av insomni er betydelig høyere blant pasienter med angst og depresjon enn i normalbefolkningen (6). Nyere forskning peker på at sammenhengen går begge veier (7,8).…”
Section: Fortolkningunclassified